The Effects of Hepatitis Therapy and Virus Resistance on Pregnant Women: A Comprehensive Analysis (American Journal of Medical Science and Innovation, 2024)
This study aims to provide a comprehensive analysis of the effects of hepatitis therapy and virus resistance on pregnant women. Hepatitis, a liver condition that is often regarded as a viral infection, poses considerable risks during pregnancy for both the mother’s and baby’s health. In viral hepatitis (like hepatitis B or C), the risk of negative outcomes and liver damage increases dramatically for expecting women as well as for fetus health. In addition to antiviral therapy (considering the drug safety, efficacy, and resistance issue), vaccination and preventive measures are important components of the treatment process. The purpose of this manuscript is to critically examine the literature that is currently accessible to illuminate the most crucial aspects or elements and provide useful input into treatment strategy optimization for pregnant women afflicted with hepatitis. While remarkable advancements have been made, screening and diagnostic services demand improvements and illustrate the need for efficient measures to abridge the impact of this viral hepatitis on pregnant women and their newborn babies.